Endgame in the Western Sahara : what future for Africa's last colony? - Shelley, Toby. (London ; New York : Zed Books : Distributed in the USA exclusively by Palgrave, 2004)
"Toby Shelley has talked to Polisario, Moroccan, Algerian and other diplomats. He has visited the territory and had access to opposition activists and Moroccan officials. In the refugee camps he interviewed the leadership of Polisario. What emerges is that the fate of the Western Sahara is being moulded by global and regional forces and that it is the Sahrawis under Moroccan rule who are best placed to influence that fate."--Jacket.
Foreword / Jose Ramos Horta -- 1. International context : the Maghreb from 'Cold War' to 'War against Terror' -- 2. Cain and Abel : the Western Sahara and the struggle for regional supremacy -- 3. Morocco : unstable and counting the cost of the green march -- 4. The alchemist's dream : the quest for gold from the desert sand -- 5. Sahrawi society under occupation -- 6. The 'years of lead' -- 7. An identity forged by resistance -- Photographs by J.C. Tordai -- 8. 1999 : civil society and breaking down the 'wall of fear' -- 9. Zero-sum game : the Western Sahara and the UN process -- 10. Polisario and the SADR : guerrillas, refugees and their state-in-waiting -- 11. War : the unbroken chain -- 12. Endgame.
Includes bibliographical references and index.
Keywords: Since 1975; Sahrawi; Western Sahara; Self-determination.; Morocco; Western Sahara -- History -- 1975-; Sahara occidental -- Histoire -- 1975-; Western Sahara; Westsahara; History